2014
DOI: 10.1007/s11631-014-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and speciation of selenium in Cardamine sp. in Yutangba Se Mining Field, Enshi, China

Abstract: A naturally selenium-accumulating Cardamine sp. is growing in Yutangba Selenium Mining Field, Enshi area, Hubei Province, China, where the geochemical environment is selenium-enriched and endemic selenosis ever occurred in humans. The present study investigated the characteristics of accumulation, speciation and quantity of selenium in Cardamine sp. with HPLC-ICP-MS. Results show that Cardamine sp. can accumulate Se at most 1427 mg/kg in seedling leaves. Even after the biomass incensement of growing up, the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The HG-AFS conditions as follows: negative high voltage 340 V, lamp current 100 mA, temperature of atomization 800 °C, a flow rate of carrier gas 500 mL min − 1 , injection volume 1 mL, KBH 4 concentration 3.5%. The inorganic Se concentration, including SeO 3 2− and SeO 4 2− , was determined via liquid chromatography–HG-AFS (LC-AFS8510, Beijing Haiguang Instrument, China) [ 2 , 58 ]. The standard substances of SeO 3 2− and SeO 4 2− were purchased from the National Institute of Metrology, China.…”
Section: Methodsmentioning
confidence: 99%
“…The HG-AFS conditions as follows: negative high voltage 340 V, lamp current 100 mA, temperature of atomization 800 °C, a flow rate of carrier gas 500 mL min − 1 , injection volume 1 mL, KBH 4 concentration 3.5%. The inorganic Se concentration, including SeO 3 2− and SeO 4 2− , was determined via liquid chromatography–HG-AFS (LC-AFS8510, Beijing Haiguang Instrument, China) [ 2 , 58 ]. The standard substances of SeO 3 2− and SeO 4 2− were purchased from the National Institute of Metrology, China.…”
Section: Methodsmentioning
confidence: 99%
“…(2014) measured concentrations of total Se by hydride generation-atomic fluorescence spectrometry (HG-AFS) and HPLC-ICP-MS, respectively. These studies showed that C. hupingshanensis could accumulate Se in excess of 1400 mg Se kg −1 of dry matter in all tissues of seedlings, with most not exceeding 4000 mg Se kg −1 of dry matter in roots 9 , 10 .…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, its super‐selenium‐rich characteristics have garnered attention in the research community in China. [ 15–19 ] In this study, we report the separation, purification, structural characterization and analysis of C. hupingshanensis polysaccharide no. 2 (CHP‐2) and its effect on diabetes.…”
Section: Introductionmentioning
confidence: 99%